PENGARUH STRATEGI PENJUALAN ONLINE, KUALITAS PELAYANAN, DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN DI KUKUME BEAUTY - Ni Putu Ikka Sanika Masdaniaty (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2024)
This research aims to investigate the influence of online sales strategies, service quality, and price perceptions on customer loyalty at Kukume Beauty. The research was conducted through a survey of 300 customers randomly selected from the Kukume Beauty database. Data was collected using a questionnaire consisting of questions related to online sales strategies, service quality, price perceptions, and level of customer loyalty. Data analysis was carried out using the multiple regression method. The research results show that online sales strategies have a significant positive influence on customer loyalty. Likewise with service quality, which also significantly influences customer loyalty. Apart from that, price perception also plays a role in forming customer loyalty, although its influence is not as big as online sales strategies and service quality.